MEAT QUALITY AND FATTY ACID COMPOSITION OF CHIOS MALE LAMBS FED UNDER TRADITIONAL AND INTENSIVE CONDITIONS - ÖNENÇ, Sibel Soycan; Özdoðan, Mürsel; Aktümsek, Abdurrahman; Taþkýn, Turgay (Emirates Journal of Food and Agriculture, 2015)
The study was conducted to compare the chemical composition, physicochemical characteristics, texture profile analysis (TPA) parameters and fatty acid composition of the meat of Chios male lambs fed under traditional and intensive conditions. A total of 34 lambs at the age of 3 months were used. The animals were randomly separated into traditional (T) and intensive (I) groups in equal numbers. The lambs in group T were fed on ration prepared in local style and grazed in olive grove for 8 h/day, while those in group I received 255 g alfalfa hay per animal and ad libitum mixed feed. The animals were slaughtered at 5 months of age. Significant differences were not found for chemical composition, physicochemical characteristics, and TPA parameters. Fatty acids such as C17: 0, C18: 0, C18: 1 Cc11, C18: 1 c9, C18: 2 c9c12, C18: 2 c9t11 and the total conjugated linoleic fatty acids in muscle differed significantly between the two groups. As a results of the study, it was found that Chios lambs fed intensively had particularly tender, vivid and bright meat however the contents of C18 fatty acid group and CLA were higher in lambs fed under traditional conditions.